Occupational and environmental medicine in Colombia (2000)
Colombia is a country rich in natural resources, with a steadily developing economy. Occupational and environmental medicine (OEM) education and practice have developed relatively recently in Colombia, mainly in response to a series of long overdue (and still partially implemented) reforms to the health care, social benefits, and education systems. Expansion in general and occupational health coverage of the Colombian population and development of OEM education and training were to be achieved through a clear stimulus to private sector initiatives. Despite some measurable overall progress, the goals remain elusive. This article discusses several aspects and the perspectives for further development of the specialty in this country, in the context of the socioeconomic factors involved in that process.